PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT JALAN HIJAU PONDOK GEDE BEKASI - Silviana Maulida; Hery Wihasnanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
To analyze the influence of leadership style and work motivation on employee job satisfaction at PT. Jalan Hijau Pondok Gede Bekasi. This research was carried out on PT. Jalan Hijau Pondok Gede Bekasi. The research method used is a clear depiction of the relationship between variables. The population in this study were employees of PT. Jalan Pondok Hijau Pondok Gede Bekasi. By using the Isaac and Michael formula was obtained. The analysis method uses simultaneous and partially linear regression. The research results show that both simultaneous and partially leadership styles and work motivation have a positive and significant effect on employee job satisfaction of PT. Jalan Pondok Hijau Pondok Gede Bekasi.